(untitled) (Journal of Plant Disease Sciences, 2025)
Brown leaf spot remains one of the most devastating diseases of rice under the present scenario, causing significant yield losses. To understand the cultural and morphological variability of the pathogen causing brown leaf spot, extensive fortnightly surveys were conducted in major rice-growing districts of Madhya Pradesh. The collected isolates were studied to assess variability under different cultural and environmental conditions. Among the culture media tested, the maximum mycelial growth of the pathogen was recorded on oat meal agar (68.45 mm), while the minimum growth was observed on corn meal agar (40.26 mm). The effect of pH on fungal growth revealed that the highest mycelial growth occurred at pH 6.5 (64.41 mm), whereas the lowest growth was recorded at pH 4.5 (38.55 mm). This study also highlights the epidemiology of brown leaf spot, the existing control measures practiced by farmers, and identifies several quantitative and qualitative gaps in disease management strategies. Addressing these gaps could significantly enhance disease control efficiency and contribute to sustainable rice production, which is crucial for improving the livelihoods of farmers under current agricultural conditions.